Effects of the Affordable Care Act on Health Behaviors after Three Years - Charles Courtemanche; James Marton; Benjamin Ukert; Aaron Yelowitz; Daniela Zapata (Institute of Labor Economics (IZA), 2018)
This paper examines the impacts of the Affordable Care Act (ACA) – which substantially increased insurance coverage through regulations, mandates, subsidies, and Medicaid expansions – on behaviors related to future health risks after three years. Using data from the Behavioral Risk Factor Surveillance System and an identification strategy that leverages variation in pre-ACA uninsured rates and state Medicaid expansion decisions, we show that the ACA increased preventive care utilization along several dimensions, but also increased risky drinking. These results are driven by the private portions of the law, as opposed to the Medicaid expansion. We also conduct subsample analyses by income and age.
Keywords: I12; I13; I18; 330; Affordable Care Act; health insurance; Medicaid; health behavior; obesity; smoking; drinking; preventive care; screening